TMJ and Related Skeleton Surgical Treatments: Proceedings of the 5th Sino-German Symposium 2024 - Stamm, Thomas; Hohoff, Ariane; Keil, Christiane; Joos, Ulrich (Archive of Orofacial Data Science, 2024)
The 5th Sino-German Symposium 2024 convened leading experts in temporomandibular joint (TMJ) disorders, hosted by Duisburg-Essen University and Shanghai Jiao Tong University. The symposium aimed to enhance collaboration and knowledge exchange between scholars from Germany and China. Attendees explored a variety of topics, including anterior disc displacement, condylar resorption, and advanced surgical techniques for TMJ. Session I addressed anterior disc displacement and condylar resorption, highlighting both surgical and conservative treatment options alongside the utility of MRI for radiological diagnoses. Session II focused on the complexities of condylar fractures and ankylosis, discussing treatment protocols and soft tissue management, with considerable dialogue surrounding the Shanghai protocol for ankylosis. Session III examined TMJ reconstruction methods, including costochondral grafts and alloplastic replacements, emphasizing the need to balance innovative approaches with established surgical practices. Finally, Session IV tackled clinical issues related to TMJ and cranio-jaw interactions, including complications from TMJ prostheses and multidisciplinary approaches to complex cases. The symposium was co-organized by key organizations such as German Surgical Foundation, Chinese Stomatological Association, Chinese Society of Oral and Maxillofacial Surgery and the National Clinical Research Center for Oral Diseases (Shanghai), China, highlighting its collaborative nature. The proceedings aim to advance the understanding and treatment of TMJ disorders, ultimately benefiting both practitioners and patients in the field.